Tuberculosis of the Parotid Gland. (8th August 2012) - Gupta, Vivek; Patankar, Kiran; Shinde, Archana; Bhosale, Charu; Tamhane, Ajitey
Abstract : Parotid gland involvement is extremely rare, even in countries in which tuberculosis is endemic. Clinically, it usually presents as a slow-growing mass indistinguishable from a malignancy. On imaging too, tuberculosis of the parotid may mimic neoplasm. The diagnosis of parotid tuberculosis needs a high degree of clinical suspicion. This paper highlights the clinical presentation, imaging findings, and importance of FNAC in diagnosis of this rare entity.